2019
DOI: 10.3390/rs11070886
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Source Data Fusion Based on Ensemble Learning for Rapid Building Damage Mapping during the 2018 Sulawesi Earthquake and Tsunami in Palu, Indonesia

Abstract: This work presents a detailed analysis of building damage recognition, employing multi-source data fusion and ensemble learning algorithms for rapid damage mapping tasks. A damage classification framework is introduced and tested to categorize the building damage following the recent 2018 Sulawesi earthquake and tsunami. Three robust ensemble learning classifiers were investigated for recognizing building damage from Synthetic Aperture Radar (SAR) and optical remote sensing datasets and their derived features.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 43 publications
(50 reference statements)
0
45
0
2
Order By: Relevance
“…C-band (wavelength of 5.6 cm) Sentinel-1 SAR data were provided freely by the European Space Agency. These post-event data have been used for rapid building damage mapping for this event [23]. However, due to the short wavelength, the Sentinel-1 SAR coseismic interferograms show strong decorrelation in this area, so they were not used in this study.…”
Section: Alos-2 Sar Data and Processingmentioning
confidence: 99%
“…C-band (wavelength of 5.6 cm) Sentinel-1 SAR data were provided freely by the European Space Agency. These post-event data have been used for rapid building damage mapping for this event [23]. However, due to the short wavelength, the Sentinel-1 SAR coseismic interferograms show strong decorrelation in this area, so they were not used in this study.…”
Section: Alos-2 Sar Data and Processingmentioning
confidence: 99%
“…An important constraint is the availability of a pre-event image. To the best of our experience, a temporal baseline from few months to about a year performs fairly well to identify damages in urban areas [12][13][14][15][16][17][18]. However, other types of land use may exhibit constant and systematic changes through time.…”
Section: Introductionmentioning
confidence: 94%
“…The evaluation was made in the use of a random forest [55] and two further modifications termed as rotation forest [97] and canonical rotation forest [98]. The classifiers were used to identify the building damage during the 2018 Sulawesi, Indonesia earthquake tsunami.…”
Section: Decision Trees and Random Forest Classifiersmentioning
confidence: 99%
“…The damage map provided by the Copernicus Emergency Management Service were used as training data [99]. The proposed framework learned the damage patterns from a limited available human-interpreted building damage annotation and expands this information to map a larger affected area [55]. Table 3 summarized the studies reported in this chapter.…”
Section: Decision Trees and Random Forest Classifiersmentioning
confidence: 99%
See 1 more Smart Citation